2016
DOI: 10.1111/jpy.12367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium sulfate on the freshwater microalgaChlamydomonas moewusii: implications for the optimization of algal culture media

Abstract: The study of the microalgal growth kinetics is an indispensable tool in all fields of phycology. Knowing the optimal nutrient concentration is an important issue that will help to develop efficient growth systems for these microorganisms. Although nitrogen and phosphorus are well studied for this purpose, sulfur seems to be less investigated. Sulfate is a primary sulfur source used by microalgae; moreover, the concentration of this compound is increasing in freshwater systems due to pollution. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…Sulfur removal from wastewater by microalgae, like other pollutants such as nitrate and phosphate, is a possibility owing to the assimilation of sulfur in synthesizing amino acids cysteine and methionine [18]. Figure 5 shows changes in the concentration of sulfate during the cultivation of the different microalgae species under different growth medium.…”
Section: Sulfate Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur removal from wastewater by microalgae, like other pollutants such as nitrate and phosphate, is a possibility owing to the assimilation of sulfur in synthesizing amino acids cysteine and methionine [18]. Figure 5 shows changes in the concentration of sulfate during the cultivation of the different microalgae species under different growth medium.…”
Section: Sulfate Removalmentioning
confidence: 99%
“…compared to other wastewater samples evaluated in the study. Mera et al[18] reported sulfate concentration of 14.2 mg/L as the optimal growth sulfate requirement and concentration higher than 426.12 mg/L produced a toxic effect, not due to the presence of excess sulfate ions, but due to increased ionic strength of the medium. The importance of sulfate to microalgae growth was demonstrated by Lv et al[19], in which the authors recorded a maximum biomass concentration of 325 mg/L in 271 mg/L sulfate in wastewater against 137 mg/L in wastewater without sulfate.…”
mentioning
confidence: 99%
“…This study focuses on the micronutrients iron and sulfur because they are constituents of enzymes required for nitrogen utilization by microalgae (Padmavathi et al 2008;Shibagaki and Grossman Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10811-019-01915-5) contains supplementary material, which is available to authorized users. 2008) and reported to have impacts on microalgal growth (Yeesang and Cheirsilp 2011;Mera et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur is also essential for microalgal growth as it is required for the production of proteins, lipids, and polysaccharides (Shibagaki and Grossman 2008). The addition of sulfate as a source of sulfur has been shown to increase microalgal biomass production as well as nitrogen and phosphorus removal efficiencies (Mera et al 2016;Lv et al 2017). The highest biomass concentration of Chlamydomonas moewusii was obtained in a medium with ammonium as the nitrogen source when sulfur concentrations were between 3.2-96 mg L −1 (Mera et al 2016), while the final Chlorococcum sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation